Investigation of a three-phase-single-phase induction electric drive under stochastic loads - Yu.V. Shurub (National Technical University "Kharkiv Polytechnic Institute", 2014)
A control system for a three-phase-single- phase induction electric drive with a controlled phase-shifting module is developed and studied to result in a symmetric regime under stochastic load variations.